"Legalization" of the settlements of runaway monastic serfs after the first revision (based on the materials from the Simbirsk Volga region) - Pankrat, Ivan Alekseevich (Исторический журнал: научные исследования, 2025)
The article deals with the process of "legalizing" runaway monastic serfs settled in the Simbirsk Uyezd (Volga region). They were recorded during the first revision (census) in the early 1720s, but contrary to tradition, they were not deported to their former residence. The formal opportunity for this was provided by Peter the Great's resolution of February 9, 1723: "where there are entire villages, or where half or a third, the runaway serfs are to be returned to their landlords with lands, and where less, they are to be deported as others". The subject of the research are the methods of "legalization": the legal formalization of newly emerged monastic land tenure as well as the duties imposed on the peasants by the landlords. The article also pays attention to the features of settlement of runaways and their descendants in the Simbirsk Uyezd. The research methodology is based on the comparative analysis of officer inventories and revision records of the first three censuses. With these sources we can discover settlements where runaway serfs and their descendants lived, and then we are able to reconstruct the emergence of these settlements. During the reconstruction, a cartographic method was used as all revealed settlements were localized on a map in the QGIS. The study revealed that most of the "legalized" monastic estates did not meet the criteria defined by Peter the Great's resolution. There were only 6 villages of total 50 ones where runaway serfs made up more than a third of the inhabitants. The ways of legal formalization of monastic land tenure depended on the landowner whose lands the fugitives settled in. On manorial lands it was formalized by a private law transaction, and in yasak villages it was nothing more than a share in the usage of common land. The land ownership of the Nizhny Novgorod Pechersky Monastery was based on the seizure of empty land by runaways that was not formalized by any official documents. Most of the returned serfs paid money dues to their monasteries. Meanwhile, de facto some runaways did not submit their formal landlords and did not fulfill any obligations towards them.